2023
DOI: 10.3390/ijms24097910
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis and Inflammation: Insights from the Theory of General Pathological Processes

Abstract: Recent advances have greatly improved our understanding of the molecular mechanisms behind atherosclerosis pathogenesis. However, there is still a need to systematize this data from a general pathology perspective, particularly with regard to atherogenesis patterns in the context of both canonical and non-classical inflammation types. In this review, we analyze various typical phenomena and outcomes of cellular pro-inflammatory stress in atherosclerosis, as well as the role of endothelial dysfunction in local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 566 publications
0
31
0
1
Order By: Relevance
“…AS is a multidimensional inflammatory disease characterized by complex molecular and cellular changes inside the artery wall (Blagov et al, 2023;Rubin et al, 2012;Sazonova et al, 2021). Inflammation is crucial in the onset, development, and pathophysiology of AS (Gusev & Sarapultsev, 2023;Wolf & Ley, 2019). As a result, HUVECs were used in this study due to their importance in vascular endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…AS is a multidimensional inflammatory disease characterized by complex molecular and cellular changes inside the artery wall (Blagov et al, 2023;Rubin et al, 2012;Sazonova et al, 2021). Inflammation is crucial in the onset, development, and pathophysiology of AS (Gusev & Sarapultsev, 2023;Wolf & Ley, 2019). As a result, HUVECs were used in this study due to their importance in vascular endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…Inulin has been demonstrated to decrease inflammation and plasma lipid levels, thereby inhibiting AS development. [19] Mannan oligosaccharides (MOS) are consisted of up to 10 mannose units linked via 𝛼- (1,6)or 𝛽- (1,4)bonds. They are produced from mannans present in the outer cell wall membranes of bacteria, plants, or yeast.…”
Section: Wwwadvancedsciencenewscom Wwwmnf-journalcommentioning
confidence: 99%
“…[ 3 ] The released cytokines and chemokines cause continuous inflammation, recruit inflammatory cells, and form atherosclerotic plaques, ultimately leading to the systemic activation of inflammatory pathways such as toll‐like receptors and the inflammasome. [ 4 ] Inflammatory signals affect permeability pathways and increase intestinal permeability, thus leading to the leakage of bacterial components into the circulatory system from the mesenteric veins and alteration of immune interactions in the gut. Increased levels of inflammatory factors act on target organs and tissues, ultimately leading to inflammation and disease.…”
Section: Introductionmentioning
confidence: 99%
“…Skin thickness in SSc often spontaneously improves over time, confounding many interventional studies, as recently reported with belimumab and nintedanib [184][185][186][187][188][189][190][191][192]. However, mycophenolate, cyclophosphamide, and methotrexate have been shown to improve the mRss and reduce skin thickness in SSc [184][185][186][187][188][189][190][191][192]. Methotrexate has always been problematic in SSc as it can occasionally cause lung inflammation that can be confused with SSc-ILD [184][185][186][187][188][189][190][191][192].…”
Section: Biomarkers In Systemic Sclerosis Skin Involvementmentioning
confidence: 99%
“…However, mycophenolate, cyclophosphamide, and methotrexate have been shown to improve the mRss and reduce skin thickness in SSc [184][185][186][187][188][189][190][191][192]. Methotrexate has always been problematic in SSc as it can occasionally cause lung inflammation that can be confused with SSc-ILD [184][185][186][187][188][189][190][191][192]. Recently, tofacitinib, although not approved for SSc, has been shown to be more effective than methotrexate in reducing the mRss, ultrasound skin thickness, and musculoskeletal symptoms, and in reducing the biomarker genes regulated by the interferon in SSc [184][185][186][187][188][189][190][191][192].…”
Section: Biomarkers In Systemic Sclerosis Skin Involvementmentioning
confidence: 99%